STATIC PERFORMANCE CHARACTERISTICS OF VORTEX RATE SENSOR (Journal of Engineering, 2011)
The vortex rate sensor is a fluidic gyroscope with no moving parts and can be used in very difficultconditions like radiation, high temperature and noise with minimum cost of manufacturing andmaintenance. A vortex rate sensor made of wood has been designed and manufactured to studytheoretically and experimentally its static performance .A rig has been built to carry out the study,the test carried out with three different air flow rates (100, 150, and 200 l/min).The results show thatthe relation between the differential pressure taken from the sensor pickoff points and the angularvelocity of the sensor was linear.The present work involved theoretical and experimental study ofvortex rate sensor static characteristics .Vortex rate sensor has been designed and manufacturedwith dimensions-:Radius of vortex chamber= 140 mm, Radius of sink tube rs= 4.5 mm, the pickoff hole diameter =2mm, Height of vortex chamber b= 19 mm, Height of pickoff pipe h= 25 mm.